Temporal distribution and insecticide resistance profile of two major arbovirus vectors Aedes aegypti and Aedes albopictus in Yaoundé, the capital city of Cameroon - Basile Kamgang (Parasites & Vectors, 2017)
Abstract Background Aedes aegypti and Ae. albopictus are the major epidemic vectors of several arbovirus diseases such as yellow fever, dengue, Zika and chikungunya worldwide. Both Aedes vectors are presents in Cameroon; however, knowledge on the dynamic of the distribution of these species across cities and their resistance profile to insecticide are limited. Here, we assessed the current distribution of Ae. aegypti and Ae. albopictus in Yaoundé, the Capital City, established the resistance profile to insecticides and explored the resistance mechanisms involved. Methods Immature stages of Aedes were sampled in several breeding sites in December 2015 (dry season) and June 2016 (rainy season) in three central neighborhoods and four peripheral neighborhoods and reared to adult stage. The G0 adults were used for molecular identification and genotyping of F1534C mutation in Ae. aegypti. Bioassays and piperonyl butoxide (PBO) assays were carried out according to WHO guidelines. Results Analysis revealed that both species Ae. aegypti and Ae. albopictus are present in all prospected sites in Yaounde. However, in the dry season Ae. aegypti is most abundant in neighborhoods located in downtown. In contrast, Ae. albopictus was found most prevalent in suburbs whatever the season and in downtown during the rainy season. Bioassay analysis showed that both Ae. aegypti and Ae. albopictus, are resistant to 0.05% deltamethrin, 0.1% bendiocarb and 4% dichlorodiphenyltrichloroethane (DDT). A decreased of susceptibility to 0.75% permethrin and a full susceptibility to malathion 5% was observed. The mortality rate was increased after pre-exposure to synergist PBO. None of Ae. aegypti assayed revealed the presence of F1534C mutation. Conclusion These findings are useful to planning vector control programme against arbovirus vectors in Cameroon and can be used as baseline in Africa where data on Aedes resistance is very scarce to plan further works.